Contribution of extrahepatic collaterals to liver parenchymal circulation after proper hepatic artery embolization. Issue 7 (15th July 2014) - Mine, Takahiko; Murata, Satoru; Ueda, Tatsuo; Takeda, Minako; Onozawa, Shiro; Yamaguchi, Hidenori; Kawano, Youichi; Kumita, Shin‐ichiro
Abstract Background and Aim To retrospectively evaluate proper hepatic artery embolization, with respect to the development of extrahepatic collaterals. Methods Proper hepatic artery embolization was performed in 18 patients with hemorrhagic arterial lesions in the hepatic hilum. Post‐procedural development of extrahepatic collaterals was evaluated by computed tomography or angiography. Embolization data and liver function tests were assessed. The correlation of outcomes with portal venous stenosis, hepatic failure prior to embolization, elevation of prothrombin time, and insufficient collateral development were analyzed. Results Postoperative bleeding occurred in 17/18 patients, and one was treated for an idiopathic aneurysm of the proper hepatic artery; all treatments achieved technical success. Extrahepatic collaterals were confirmed in 13 patients. Elevations of liver function test values were transient and returned to baseline within 14 days in patients with collateral development (n = 13), but were unimproved in patients without collaterals (n = 5) (P < 0.001). Portal venous stenosis; prior hepatic failure; unrecovered, elevation of prothrombin time; and insufficient collateral development were significantly correlated with poor outcomes (P < 0.05, respectively). Conclusions Proper hepatic artery embolization is effective for hemostasis, and extrahepatic collateral development is expected. Therefore, this is a safe treatment without prolonged hepatic ischemic damage, especially in patients without severe portal venous stenosis or prior hepatic failure.